PENGARUH PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM ABDUL WAHAB SYAHRANIESAMARINDA - Eka Yudhyani, Winda Aprila, Theresia Militina, (EKONOMIA, 2015)
Winda Aprila, 2015, Effect Against kepusan Services Outpatient in General Hospital Abdul Wahab yahranie Samarinda, under the guidance of Mrs. Theresia Militina and Mrs. Eka Yudhyani.Efforts to achieve patient satisfaction is not easy, this is due to patient satisfaction may not be achieved even if only temporarily. But the repair or improvement of patient satisfaction can be done in various ways. In principle, patient satisfaction strategy causes the competitor must work hard and requires a high cost in his bid for the trustthe public. A. Wahab Syahranie Hospital as the hospital referral hospitals in East Kalimantan should pmemperhatikan patient satisfaction.The purpose of this study was to examine the effect between the level of patient satisfaction with the service of vulnerable road General Hospital Syahranie Abdul Wahab. The population in this study were outpatients who come to the period of 15 April - May 14, 2015 by using the technique of accidental sampling up to 150 samples / respondents.Basic theory used is the Marketing Management by using multiple linear regression analysis.The results showed: 1. Function regression calculation result is Y = 0.403 + 0.133 + 0.187 X1 X2 X3 + 0.149 + 0.221 + 0.197 X X4, fully regression coefficient is positive, meaning that if there is improvement of the quality of variable reliability, responsiveness, assurance, attention and physical form it will increase patient satisfaction hospital outpatient A. Wahab Syahranie2. The value of R = 0,793 ( 79.3 %) Show the correlation are strong enough to satisfaction an outpatient hospital common A. Wahab Syahranie Samarinda.3. The value of the coefficient of determinan (R2) 0.629 (62.9%) show the quality of service that strong enough to determine the sastisfaction of an outpatient hospital A. Wahab Syahranie Samarinda4. Guarantee have the influence of the dominant castes, this is in evidenced by the value of bulish t valiable guarantee of 6.651 of bulish t a variable other